2015
DOI: 10.1158/1535-7163.mct-14-0849
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Kinase Inhibitors Imatinib and Dasatinib Reduce Myeloid Suppressor Cells and Release Effector Lymphocyte Responses

Abstract: Immune escape mechanisms promote tumor progression and are hurdles of cancer immunotherapy. Removing immunosuppressive cells before treatment can enhance efficacy. Tyrosine kinase inhibitors (TKI) may be of interest to combine with immunotherapy, as it has been shown that the inhibitor sunitinib reduces myeloid suppressor cells in patients with renal cell carcinoma and dasatinib promotes expansion of natural killer-like lymphocytes in chronic myeloid leukemia (CML). In this study, the capacity of dasatinib and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 37 publications
1
59
1
1
Order By: Relevance
“…This complex crosstalk in CRC, we propose, can be investigated by implementing a combination of sophisticated informatics, -omics technologies and in vivo studies in a spatio-temporal manner, coupled with larger protein tracking and interaction studies. Emerging multiplexed technologies such as SOMAmer 1 [170], proximity extension assays [35,171] and/or SureFire 1 assays [172] will be crucial in the coming years to perform more elaborate experiments in order to elucidate complex cell signaling behaviors within a matrix of different pathways and the crosstalk between them. It is crucial to remember that in cancer and various diseases, we cannot study these pathways in isolation but instead must transition into a matrix-oriented systems approach that more comprehensively models the spatio-temporal ramifications of signaling activities within the complexity of living cells and tissues.…”
Section: Resultsmentioning
confidence: 99%
“…This complex crosstalk in CRC, we propose, can be investigated by implementing a combination of sophisticated informatics, -omics technologies and in vivo studies in a spatio-temporal manner, coupled with larger protein tracking and interaction studies. Emerging multiplexed technologies such as SOMAmer 1 [170], proximity extension assays [35,171] and/or SureFire 1 assays [172] will be crucial in the coming years to perform more elaborate experiments in order to elucidate complex cell signaling behaviors within a matrix of different pathways and the crosstalk between them. It is crucial to remember that in cancer and various diseases, we cannot study these pathways in isolation but instead must transition into a matrix-oriented systems approach that more comprehensively models the spatio-temporal ramifications of signaling activities within the complexity of living cells and tissues.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that patients with progressive disease were significantly more likely to have a decrease in ALC during treatment than were patients with stable disease. Notably, imatinib has been shown to decrease the number of myeloid suppressor cells and improve the responsiveness of T-cells [14]. The decrease in ALC in patients with progression may be representative of a failure to generate an improved systemic T-cell response rather than a suppressive effect of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor infiltration by these immune cells was associated with improved progression-free survival in association with KIT exon 11 mutations. More recent data suggest that tyrosine kinase inhibitors can induce a Th1-specific T-cell response [13] and reduce myeloid-derived suppressor cells, both of which are thought to promote antitumor immune activity [14]. Furthermore, imatinib therapy has been shown to enhance tumor-antigen presenting cell function [15].…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of administration of immune treatment and targeted therapy is important. In addition, mRCC patients, who discontinued the treatment of PD-1 inhibitor either in monotherapy or combined with CTLA-4 inhibitor/VEGFR-TKI, could still get the benefits from subsequent VEGFR-TKI therapy without increase of toxicity [7]. Accumulating evidence suggests that RCC is amenable to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%